Thyroid Disorders in Pregnancy: Role of Routine Antenatal Thyroid Screening (Ibrahim Cardiac Medical Journal, 2021)
Background & objective:Thyroid disorders are among the common endocrine problems during pregnancy with well-known adverse effects on both mother and fetus. Many of these adverse effects could be prevented or ameliorated by early detection and appropriate treatment of conditions, provided routine antenatal thyroid screening is done. Considering this view, the present study was aimed to find the prevalence of thyroid disorders and their spectrum in pregnancy in order to justify the necessity of routine antenatal thyroid screening.Methods: This cross-sectional study was conducted in the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period 1 year from July 2012 to June 2013 on pregnant women to screen for the thyroid disorders in pregnancy. Based on predefined eligibility criteria, a total of 246 pregnant women up to 36 weeks of gestation were consecutively included in the study. A short history with brief physical examination was done followed by collection of blood samples. Thyroid function was assessed by measuring serum levels of thyroid stimulating hormone (TSH). Serum free thyroxin (FT4) level was estimated in 71 cases, where TSH value was deranged. Trimester specific reference range of serum TSH was used to define hypothyroid, euthyroid and hyperthyroid cases. The suspected risk factors were then compared between abnormal and euthyroid groups to find their association with thyroid disorders.Result: The results of the study showed that the overall prevalence of abnormal thyroid function status was 30.9% (hypothyroidism 29.7% and hyperthyroidism 1.2%) based on normal range of serum TSH in different trimesters of pregnancy. Pregnant women with thyroid disorders were generally older than their euthyroid counterparts (p = 0.039). Hypothyroid state was fairly common with advancing gestation (21.3%, 30.3% and 34% in the 1st, 2nd, and 3rd, trimesters respectively). Pregnant women with personal or family history of thyroid disease in the past exhibited a higher prevalence of abnormal thyroid function than those who did not have such history (p = 0.041 and p = 0.044 respectively). Past menstrual irregularity, past history of subfertility or abortion were significantly associated with thyroid disorders (p = 0.042, p = 0.004 and p < 0.001 respectively). Presence of goitre (21.1%) in current pregnancy also showed significant association with thyroid dysfunction (p = 0.001). The risk of developing abnormal thyroid function was observed to be 3.6(95% CI = 1.9 – 6.4) times higher in those who had at least one risk factor than those who did not have any risk factors (p < 0.001). However, a sizable portion (27.6%) of pregnant women without any risk factors developed abnormal thyroid function.Conclusion: The study concluded that one in every three women may have thyroid disorder during pregnancy, primarily hypothyroidism. Adopting risk factor-based screening for thyroid disorders in pregnancy, there is every chance that a substantial number of cases with thyroid dysfunction may be missed. Therefore, routine antenatal thyroid screening is recommended.Ibrahim Card Med J 2020; 10 (1&2): 74-83